(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Because of difficulty of Reconstructing 3D surface from the 2D captured images in terms of getting a higher resolution compared with the original surface so it has been adopted treatment of surface images after reconstructing the surface by of assembling all 2D im- ages and apply various filters to get the surface closest to the original surface of the sample under test. Various ways have been applied such as Laplacian and Median. It has been found that Median operator gave the best treatment to the surface where it was adopted to find the toolpath through the surface points for the purpose of machining using a CNC milling machine.